Nanodrug with ROS and pH Dual‐Sensitivity Ameliorates Liver Fibrosis via Multicellular Regulation. Issue 7 (14th February 2020) - Lin, Liteng; Gong, Hengye; Li, Rui; Huang, Jingjun; Cai, Mingyue; Lan, Tian; Huang, Wensou; Guo, Yongjian; Zhou, Zhimei; An, Yongcheng; Chen, Zhiwei; Liang, Licong; et al.
Abstract: Liver fibrosis currently represents a global health problem without effective pharmacotherapeutic strategies. The clinical translation of polydatin, a promising natural anti‐fibrotic drug candidate with broad anti‐inflammatory and antioxidant capabilities, remains a major challenge due to its limited water solubility and tissue absorption. Herein, a polydatin‐loaded micelle (PD‐MC) based on reactive oxygen species (ROS) and pH dual‐sensitive block polymer PEG‐P(PBEM‐ co ‐DPA) is developed. The micelle exerts great potential in improving the biocompatibility of polydatin and shows highly efficient liver‐targeted drug release in response to the fibrotic microenvironment. Both in vitro and in vivo studies demonstrate that PD‐MC can significantly suppress inflammatory response and oxidative stress, reduce hepatocyte apoptosis, and avert activation of macrophages and hepatic stellate cells. More excitingly, the blank micelle itself promotes the hepatic ROS consumption at the pathologic site to provide anti‐inflammatory benefits. These favorable therapeutic virtues of targeting multiple cell types endow PD‐MC with remarkable efficacy with minimal side effects in liver fibrosis treatment. Thus, PD‐MC holds great potential to push forward the clinical application of polydatin in pharmacotherapeutic approaches against liver fibrosis. Abstract : A reactive oxygen species and pH dual‐sensitive polydatin‐encapsulated micelle (PD‐MC) is developed for liver‐targeted drug release in response to the fibrotic microenvironment for the treatment of liver fibrosis. In vitro and in vivo results demonstrate that PD‐MC ameliorates liver fibrosis by suppressing inflammatory response and oxidative stress, reducing hepatocyte apoptosis, and averting activation of macrophages and hepatic stellate cells.